Ambliopia y su influencia en el aprendizaje de los niños de 6 a 7 años de la Unidad Educativa Adolfo María Astudillo Babahoyo Los Ríos, periodo mayo – septiembre 2019 - Guamán Olvera, Adriana Verónica (2019)
Introduction: Amblyopia is frequently cited as the main cause of visual loss in childhood, its incidence is between 1 and 4% of the population. Amblyopia is a term that is classically defined as a decrease in visual acuity in one or both eyes without an organic lesion. Objective: Analyze the influence of amblyopia on the learning of children from 6 to 7 years of the Educational Unit Adolfo Maria Astudillo Babahoyo Los Ríos Educational Unit, period May - September 2019. Methodology: A cross-sectional study was carried out on seventh-year-old children of the Educational Unit “Adolfo María Astudillo, the sample consisting of 17 students, which was characterized by sex, severity, type of amblyopia, refractive problems. The information was collected in the medical records. Result: male sex prevailed with 64% refractive amblyopia was the most frequent, the degree of severity was moderate, the average age in children with amblyopia was 7 years, symptoms that are frequent amblyopia and difficult school learning in children from 6 to 7 years old, it was due to blurred vision with 47%. Conclusion: The influence of amblyopia on the learning prejudices the academic performance of the students, given the lack of knowledge on the part of the parent for their early detection.